2023
DOI: 10.1021/acsabm.2c00910
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly in an Experimentally Realistic Model of Lobed Patchy Colloids

Abstract: Colloids with lobed architectures have been shown to self-assemble into promising porous structures with potential biomedical applications. The synthesis of these colloids via experiments can be tuned to vary the number and the position of the lobes. However, the polydispersity involving the numbers, sizes, and the dispositions of lobes, that is often observed in particle designs, can significantly affect their self-assembled structures. In this work, we go beyond the uniform lobe size conditions commonly cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
(115 reference statements)
0
5
0
Order By: Relevance
“…Self-assembled peptide materials possess a series of advantageous properties, particularly in their ability to form different types of nanostructures which can potentially serve as drug nanocarriers for drug release applications. , Therefore, a promising direction in cancer therapeutics is the design of new peptide materials that can be self-assembled for the encapsulation of cancer drugs . The intrinsic benefits of peptide self-assembled materials and the growing advances in computational and experimental approaches in the study and design of self-assembled systems could serve as a means to design new classes of cancer drug delivery systems which may provide further alternatives to existing approaches. Additionally, they can serve as stepping stones for designing systems comprising peptide self-assembled materials, along with other materials for the delivery of cancer drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Self-assembled peptide materials possess a series of advantageous properties, particularly in their ability to form different types of nanostructures which can potentially serve as drug nanocarriers for drug release applications. , Therefore, a promising direction in cancer therapeutics is the design of new peptide materials that can be self-assembled for the encapsulation of cancer drugs . The intrinsic benefits of peptide self-assembled materials and the growing advances in computational and experimental approaches in the study and design of self-assembled systems could serve as a means to design new classes of cancer drug delivery systems which may provide further alternatives to existing approaches. Additionally, they can serve as stepping stones for designing systems comprising peptide self-assembled materials, along with other materials for the delivery of cancer drugs.…”
Section: Discussionmentioning
confidence: 99%
“…This calculation is performed for all combinations of the particles j and k in the first coordination shell of the particle i . The probability distribution of the relative neighbor orientation, P­(θ jik ), informs on the spatial arrangements of particles in the self-assembled structures …”
Section: Models and Methodsmentioning
confidence: 99%
“…For example, Paul and Vashisth reported that the binary mixtures of snowman and dumbbell particles can form random aggregates, liquid droplets, or crystalline structures, based solely on the different sizes of their lobes. This observation is also supported by the results reported by Kalapurakal et al, where the sizes of the lobes determined the number of bonds that particles formed, thereby resulting in different self-assembled morphologies. The lobe sizes of the particles also played a role in altering the porosity of these self-assembled structures.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations